2015
DOI: 10.1002/ca.22614
|View full text |Cite
|
Sign up to set email alerts
|

Internal rib structure can be predicted using mathematical models: An anatomic study comparing the chest to a shell dome with application to understanding fractures

Abstract: The human rib cage resembles a masonry dome in shape. Masonry domes have a particular construction that mimics stress distribution. Rib cortical thickness and bone density were analyzed to determine whether the morphology of the rib cage is sufficiently similar to a shell dome for internal rib structure to be predicted mathematically. A finite element analysis (FEA) simulation was used to measure stresses on the internal and external surfaces of a chest-shaped dome. Inner and outer rib cortical thickness and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that the different ribs of the rib series are subject to contrasted mechanical stresses (e.g. as a result of locomotion or posture: Fujiwara et al ., ; Casha et al ., ), which is likely to affect their cortical thickness (Casha et al ., ). Lifestyle adaptations could also affect preferentially certain zones of the rib series depending on the taxa considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that the different ribs of the rib series are subject to contrasted mechanical stresses (e.g. as a result of locomotion or posture: Fujiwara et al ., ; Casha et al ., ), which is likely to affect their cortical thickness (Casha et al ., ). Lifestyle adaptations could also affect preferentially certain zones of the rib series depending on the taxa considered.…”
Section: Discussionmentioning
confidence: 99%
“…Within the rib series, the various elements usually show differences in morphologies and microstructures that may reflect their mechanical loads (Fujiwara et al ., ; Waskow & Sander, ; Casha et al ., , b). However, identifying the rib most affected by the mechanical load and the lifestyle is difficult because it depends on diverse factors such as locomotion mode and posture, and the identity of the optimal rib (for our purpose) may thus be variable between taxa (Bramble & Carrier, ; Fujiwara et al ., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some physiological processes are more efficient when handled by a pressure based process e.g., ventilation is more efficient in mammals than insects where it is limited by diffusion, permitting an increase in maximum body size. The torso in effect becomes a pressure vessel with limbs, with the ribs undergoing morphological changes including external dimensions, cortical thickness and bone density typical of a pressure vessel (23,24). Figure 1 A set of seven physiological rules applied to pressure-based organs or organ systems showing isometry.…”
Section: Physiological Rules Pressure-based Organsmentioning
confidence: 99%